(untitled) (The Review of Diabetic Studies, 2024)
Background: Remote Patient Monitoring is an important component of telenursing especially related to Chronic Disease Management because it gives patients engagement in their own health treatment and monitoring. Chronic conditions, such as diabetes mellitus or hypertension, require continual monitoring and management, so chronic conditions suit remote monitoring interventions well. By the virtue of this study the researcher had tried to touch all the related aspects of remote monitoring of chronic diseases, role of nursing in the same and ways and means used in this process. Study Objectives: The broader objective of the research is to conduct a systematic review and synthesize the evidence to date that explores tele-nursing and remote monitoring technologies for chronic disease management in Saudi Arabia. Materials and Methods: Study is a narrative based review study and uses exploratory research design where the data is gathered from various sources on the basis of pre decieded criteria of inclusion and exclusion. PRISMA is used to segregate and screen the collected studies. The results are presented in theoretical and chronological manner to give the clear picture of point in question. Results: The positives of this technology path are evident, but challenges in the form of literacy in technology, equity of technology infrastructure across the Kingdom, cultural considerations, and regulatory clarity will need to be addressed before telenursing can thrive.